2020
DOI: 10.5152/eurjrheum.2020.19159
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rapidly progressive osteoarthritis of the hip in its early stage

Abstract: The aim of the European Journal of Rheumatology is to cover various aspects of rheumatology for its readers, encompassing the spectrum of diseases with arthritis, musculoskeletal conditions, autoinflammatory diseases, connective tissue disorders, osteoporosis, translational research, the latest therapies and treatment programs. European Journal of Rheumatology publishes original articles, invited reviews, case based reviews, letters to the editor and images in rheumatology. The publication language of the jour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
0
26
0
1
Order By: Relevance
“…Studies also found higher levels of MMP3 in the serum and synovial fluid of patients with hip OA secondary to DDH. 11 , 12 Therefore, the expression of the MMP family of proteins may differ among different tissues in patients with DDH and during different pathological stages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also found higher levels of MMP3 in the serum and synovial fluid of patients with hip OA secondary to DDH. 11 , 12 Therefore, the expression of the MMP family of proteins may differ among different tissues in patients with DDH and during different pathological stages.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Recent studies have shown that femoral head destruction within 12 months following the disease onset may be linked to increased posterior PT in patients with RDC. 6,7 Patients with spinal disorders present the interaction between the sagittal spinopelvic alignment (SSPA) and the compensatory mechanism. 8 Of SSPA parameters, 9 pelvic incidence (PI) is a fixed fundamental anatomical parameter of the pelvis since the sacroiliac joint has limited mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Using an anteroposterior pelvic radiograph in a supine position, previous studies have shown possible relationship of RDC progression with increased posterior PT. 6,7 However, pelvic inclination may alter from a supine to a standing position. 12 The whole spinopelvic radiograph in a standing position is required for accurate assessment of the effect of SSPA on disease progression in the early stage of RDC.…”
Section: Introductionmentioning
confidence: 99%
“…If the surface of acetabular is too small or tilts for a long time, the femoral head cannot be completely covered. Therefore, it will lead to uneven pressure, which will develop into irreversible osteoarthritis in the end (Yasuda et al, 2020 ). Early screening of hip dysplasia for adults followed by proper clinical management can not only save medical resources but also keep patients away from the pain of operation (Gala et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%